2019
DOI: 10.7150/thno.34377
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Nanotherapy for Targeted Treatment of Colon Cancer by Simultaneously Regulating Tumor Microenvironment

Abstract: Colitis-associated colon cancer (CAC) is a widely recognized cancer, while treatment with the existing chemotherapeutic drugs affords limited clinical benefits. Herein we proposed a site-specific, combination nanotherapy strategy for targeted treatment of CAC by the oral route. Methods : A reactive oxygen species (ROS)-responsive and hydrogen peroxide-eliminating material OCD was synthesized, which was further produced into a functional nanoparticle (OCD NP). The antioxidative stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…In addition, Cy7.5‐AON exhibited significantly higher accumulation in the diseased colon, compared to Cy7.5‐APN (Figure S8, Supporting Information). This can be explained by the adhesive property of OxbCD, as demonstrated in our previous studies …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, Cy7.5‐AON exhibited significantly higher accumulation in the diseased colon, compared to Cy7.5‐APN (Figure S8, Supporting Information). This can be explained by the adhesive property of OxbCD, as demonstrated in our previous studies …”
Section: Resultssupporting
confidence: 57%
“…Compared to ROS‐responsive nanocarriers based on other materials, such as poly(propylene sulfide), selenium‐containing copolymers, polydopamine, and materials bearing polythioether ketal or thioketal linkers, OxbCD‐derived NPs are highly sensitive to H 2 O 2 . More importantly, our comprehensive in vitro and in vivo studies have revealed good safety profile for nanocarriers based on OxbCD . Consequently, we hypothesize that the ROS‐responsive nanocarrier ON can revive orally delivered Ac2‐26 by protecting it from degradation and selective release in the inflamed colon of IBD.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, nanoparticles based on PBAP-conjugated cyclodextrin materials can effectively eliminate H 2 O 2 , thereby inhibiting inflammatory responses and oxidative stress in stimulated macrophages . These H 2 O 2 -eliminating cyclodextrin nanoparticles efficaciously alleviated the symptoms of peritonitis and colitis in mice, by reducing the counts of neutrophils and macrophages as well as inhibiting the secretion of pro-inflammatory cytokines, chemokines, and oxidative mediators Zhang Q. et al, 2019). Also, we found that nanoparticles prepared from a luminol-conjugated ÎČ-CD material (LCD) can inhibit inflammatory response, oxidative stress, and recruitment of neutrophils and macrophages .…”
Section: Nanoparticles Derived From Functional Cyclodextrin Materialsmentioning
confidence: 78%
“…In all these mouse models, Tpl/OxbCD nanoparticles were more effective than Tpl/PLGA nanoparticles. In a separate study, we found that this type of H 2 O 2 -responsive and ROS-eliminating nanoparticles can potentiate in vivo antitumor activity of a ROS-responsive camptothecin-11 nanotherapy in mice with chronic colitis-associated colon cancer, by normalizing the proinflammatory microenvironment [ 320 ]. More recently, our studies showed that OxbCD nanoparticles are able to package a proresolving annexin A1-mimetic peptide Ac2-26, offering a ROS-responsive peptide nanotherapy (defined as AON) ( Fig.…”
Section: Treatment Of Inflammatory Diseases By Bioresponsive Drug Delmentioning
confidence: 99%